Approximated MILP model for AC transmission expansion planning: global solutions versus local solutions - Akbari, Tohid; Tavakoli Bina, Mohammad (IET generation, transmission & distribution, 2016)
This study presents a novel linear approximated methodology for AC-transmission expansion planning (AC-TEP). The AC-TEP can provide more precise picture of active and reactive power flow, along with the voltage profile of buses compared with DC-transmission expansion planning. While the AC-TEP is inherently a mixed-integer non-linear programming problem, this can be transformed into a mixed-integer linear programming framework by the proposed model which is based upon the binary expansion theory. The global optimality of the solution for the approximated model can be guaranteed by existing algorithms. The presented mathematical model has been successfully applied to several power systems and the results are compared with the exact AC-TEP model. Simulation results are promising and show that the proposed method is effective, reliable and accurate.